2019
DOI: 10.1016/j.ejso.2019.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Possible dose dependent effect of perioperative dexamethasone and laparoscopic surgery on the postoperative systemic inflammatory response and complications following surgery for colon cancer

Abstract: Possible dose dependent effect of perioperative dexamethasone and laparoscopic surgery on the postoperative systemic inflammatory response and complications following surgery for colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
(28 reference statements)
1
14
0
Order By: Relevance
“…A similar finding was also observed in patients undergoing oesophagogastrectomy (OR 5·24) 33 . Conversely, two doses of perioperative dexamethasone reduced the postoperative inflammatory response and complication rate in patients undergoing colectomy for cancer 34 .…”
Section: Discussionsupporting
confidence: 74%
“…A similar finding was also observed in patients undergoing oesophagogastrectomy (OR 5·24) 33 . Conversely, two doses of perioperative dexamethasone reduced the postoperative inflammatory response and complication rate in patients undergoing colectomy for cancer 34 .…”
Section: Discussionsupporting
confidence: 74%
“…A proportion of patients received postoperative nausea and vomiting prophylaxis in the form of intravenous dexamethasone during surgery, at the discretion of the consultant anesthetist. 8,12 During the study period, there was no formal perioperative blood transfusion protocol. As reported previously, 13 between June 2016 and June 2017 a preoperative iron replacement protocol was in place for the relatively small number of patients found to have true iron-deficient anemia.…”
Section: Patientsmentioning
confidence: 99%
“…A similar finding was also observed in patients undergoing oesophago-gastrectomy (OR 5.24) 42 . Yet these findings remain controversial, indeed McSorley et al reported that two doses of peri-operative dexamethasone, reduced the post-operative inflammatory response and complication rate in patients undergoing colectomy for cancer 43 . Therefore, it may be that patients with a CIPS>0, which accounted for 75% 0f all major morbidity in this study, will derive the most benefit from SIR attenutation.…”
Section: Discussionmentioning
confidence: 99%